2017
DOI: 10.1021/acs.orglett.7b02283
|View full text |Cite
|
Sign up to set email alerts
|

Aziridination of Cyclic Nitrones Targeting Constrained Iminosugars

Abstract: Rare C-7-substituted aziridinyl iminosugars can be synthesized through a short reaction sequence involving 1,3-cycloaddition of cyclic nitrones with alkynes and a Baldwin rearrangement of isoxazolines into bicyclic 2-acylaziridines. The method is efficient and completely diastereoselective, producing stable aziridinyl iminosugars in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Isomers with the methyl group equatorial are preferentially formed for both DNJ and for DMJ. In our earlier letter, we believed that minimization of gauche interactions, in the transition state influenced the stereochemical outcome . Here, there are three substituents in the forming triazoline that need to be considered herein, CH 3 , CH=CH 2 and OH or OR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isomers with the methyl group equatorial are preferentially formed for both DNJ and for DMJ. In our earlier letter, we believed that minimization of gauche interactions, in the transition state influenced the stereochemical outcome . Here, there are three substituents in the forming triazoline that need to be considered herein, CH 3 , CH=CH 2 and OH or OR.…”
Section: Resultsmentioning
confidence: 99%
“…Despite a sustained interest in discovery of drugs based on glycomimetics,, there have been only a few syntheses of imino sugars with quaternary centers. One recent example by Py and co‐workers, involved synthesis of aziridinyl imino sugars via nitrone‐alkyne cycloaddition and subsequent Baldwin rearrangement . Earlier, Dhavale and co‐workers reported α‐geminal dihydroxymethyl‐substituted piperidines by a route which included a variant of the Corey–Link reaction via suitably oxidized furanoses .…”
Section: Introductionmentioning
confidence: 99%
“…This involves highly regio-and stereoselective 1,3-cycloaddition between nitrones and alkynes, followed by Baldwin rearrangement to form bicyclic 2-acylaziridines. [59] In only a few steps, nitrone 69 was converted efficiently into C-7-aziridinyliminosugars 72b and 72c, which are potential glycosidase inhibitors (Scheme 16). The method also afforded other 1-azabicyclo[3.1.0]hexanes and 1-azabicyclo[4.1.0]heptanes, each bearing a substituent on the aziridine ring and all proving to be stable compounds.…”
Section: Metal-promoted Rearrangement Of 4-isoxazolines To 2-acylazirmentioning
confidence: 99%
“…Py et al reported recently an original strategy for the synthesis of aziridinyl iminosugars (Scheme 4). 34 The strategy is based on cycloaddition of cyclic nitrones with alkynes followed by highly diastereoselective Baldwin rearrangement. 35 Treatment of several nitrones 26 with various alkynes afforded isoxazolines which were converted to acylaziridines 28 by heating.…”
Section: Introductionmentioning
confidence: 99%
“…35 Treatment of several nitrones 26 with various alkynes afforded isoxazolines which were converted to acylaziridines 28 by heating. 34 Some representative examples are shown in Scheme 4. The scope of the synthetic approach described is relatively broad.…”
Section: Introductionmentioning
confidence: 99%